Attending to the Emotional Well-Being of the Health Care Workforce in a New York City Health System During the COVID-19 Pandemic. (August 2020) - Ripp, Jonathan; Peccoralo, Lauren; Charney, Dennis
Abstract : The COVID-19 pandemic has placed an enormous strain on health care workers, and its potential impact has implications for the physical and emotional well-being of the workforce. As hospital systems run well over capacity, facing possible shortages of critical care medical resources and personal protective equipment as well as clinician deaths, the psychological stressors necessitate a strong well-being support model for staff. At the Mount Sinai Health System (MSHS) in New York City, health care workers have been heroically providing frontline care to COVID-19 patients while facing their own appropriate fears for their personal safety in the setting of contagion. This moral obligation cannot be burdened by unacceptable risks; the health system's full support is required to address the needs of its workforce. In this Invited Commentary, the authors describe how an MSHS Employee, Faculty, and Trainee Crisis Support Task Force—created in early March 2020 and composed of behavioral health, human resources, and well-being leaders from across the health system—used a rapid needs assessment model to capture the concerns of the workforce related to the COVID-19 pandemic. The task force identified 3 priority areas central to promoting and maintaining the well-being of the entire MSHS workforce during the pandemic: meeting basic daily needs; enhancing communications for delivery of current, reliable, and reassuring messages; and developing robust psychosocial and mental health support options. Using a work group strategy, the task force operationalized the rollout of support initiatives for each priority area. Attending to the emotional well-being of health care workers has emerged as a central element in the MSHS COVID-19 response, which continues to be committed to the physical and emotional needs of a workforce that courageously faces this crisis.